Description of the female of Colocharis hungi Torréns (Hymenoptera, Eucharitidae) and identification key for the species of Colocharis - Schoeninger, Karine; Silva, Thiago S. R.; Kawada, Ricardo; Torrens, Javier (Zootaxa, 2018)
The female of Colocharis hungi Torréns (Hymenoptera: Eucharitidae) is newly described, detailing the characters that distinguish this species. In addition, we provide images and comments for C. hungi, diagnoses for all species of Colocharis Heraty, a key to species, and a distribution map for the species.